The making of good leaders / Abdellah Aarab - Aarab, Abdellah (2010)
We find that we usually make the distinction between good and bad leaders by how they make decisions and control those that follow them. A good leader makes good decisions and controls the public, religious body or whoever else in a positive manor and a bad leader the opposite. That is always how we do it. The problem with this is that the basis of good and bad leadership is based on control, which is usually a breeding ground for trouble. Why do we assume leaders are those that make decisions for other people? That's the consensus we see in politics. We want to 'vote' or choose someone to be our leader that will make great decisions for us. Is it so we don't have to? Is it so we have someone to blame when things go wrong? We are starting to wonder if leadership in Malaysia is to look drastically different then what we see elsewhere and usually from what we want